Usage of Titanium Molybdenum Alloy Wires in Nasal Molding: A Case Report - Rahime Burcu Nur; Begüm Yıldız; Derya Germeç Çakan (Galenos Yayinevi, 2015)
The purpose of this case report is to present the nasoalveolar molding treatment (NAM) of an infant with complete unilateral cleft lip using a nasal stent with conventional configuration made of 0.32-inch titanium molybdenum alloy (TMA). An additional nasal stent with the same configuration was constructed of stainless steel wire, and the force application by the same activation was measured. In patients with cleft lip who benefit from NAM therapy but cannot come regularly to the weekly appointments, nasal stents made of TMA may be recommended due to lighter and continuous force application.